Hospitality, Self-Determination, and Black Refugee Students in Manitoba - Heringer, Rebeca (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
A large number of refugees come to Canada every year, supporting the government’s claims that they are encouraging of “cultural diversity.” Nonetheless, the pervasiveness of racism and the paucity of research focused on the intersectional identity of Black refugee students raises several concerns, especially in light of the White savior myth that is embedded in a White society like Canada. Based on the ethic of hospitality, self-determination theory, and the tenets of critical race theory, this case study explored the hospitality of K–12 schools for Black refugee students in Manitoba. Through the voices of five students, this research demonstrates how students’ needs for autonomy, relatedness, and competency were often threatened by racist (in)actions of teachers and classmates, thus negatively impacting their educational experience.